Comparison of 6-Month and Prolonged Dual Antiplatelet Therapy after Percutaneous Coronary Intervention with Biodegradable Polymer Everolimus-Eluting Stent. (28th September 2022) - Yoon, Yong-Hoon; Park, Gyung-Min; Roh, Jae-Hyung; Her, Sung-Ho; Lim, Seong-Hoon; Kang, Tae Soo; Lee, Seung Jin; Bae, Jang-Whan; Choi, WoongGil; Yang, Yong-Mo; Kim, Junghee; Choi, Yu Jeong; et al.
Abstract : Background . The optimal duration of dual antiplatelet therapy (DAPT) after biodegradable-polymer (BP) everolimus-eluting stent (EES) implantation remains uncertain. Methods . This study analyzed 793 patients who underwent percutaneous coronary intervention (PCI) with BP-EES in 10 cardiovascular centers in Korea between July 2016 and January 2018. Using the prescription data at 6 months post-PCI, we divided these patients into two groups, namely, short-DAPT and prolonged-DAPT groups, which underwent DAPT for 6 and > 6 months of PCI, respectively. The primary endpoint, which included mortality, myocardial infarction, or target-vessel revascularization at 2 years, was compared by propensity score (PS) matching between the two groups. Results . Out of the 793 patients, 283 matched pairs were identified by PS matching. Out of this matched population, 405 (71.6%) patients had an acute coronary syndrome. The primary endpoint did not differ in 2 years between the short-DAPT and prolonged-DAPT groups (7.5% vs. 8.3%; hazard ratio, 0.87; 95% confidential interval, 0.47–1.60; P = 0.648 ). Likewise, no difference was found regarding mortality, cardiac mortality, myocardial infarction, target-lesion failure, target-vessel failure, and bleeding events defined by the Bleeding Academic Research Consortium and Thrombolysis In the Myocardial Infarction classification. Meanwhile, one patient in the short-DAPT group had definite stent thrombosis at 364 days post-PCI. Subgroup analysis showed that several anatomical and procedural factors were not significantly related to DAPT duration. Most patients (77.4%) in both groups were prescribed clopidogrel at discharge. Conclusions . In real-world patients undergoing PCI with BP-EES, the ischemic and bleeding endpoints demonstrated no difference between 6-month and prolonged (>6 months) DAPT.